2018
DOI: 10.1002/ange.201811837
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Encoding a Lipidated Amino Acid for Extension of Protein Half‐Life in vivo

Abstract: Protein therapeutics are increasingly used to treat various diseases,y et they often suffer from short serum halflives.Anemerging strategy to extend lifetime in vivo is to attach fatty acids onto proteins to increase their binding to human serum albumin (HSA). Herein, the genetic encoding of e-Nheptanoyl-l-lysine (HepoK) is reported, which introduces afatty-acid-containing amino acid into proteins with exquisite site-specificity and homogeneity,overcoming issues associated with existing chemical conjugation me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Taking advantage of the substrate promiscuousness of the Pyl pairs, various acylation-bearing UAAs (Figure 2b), that is, ε-N-acyl-lysines, such as ε-N-formyllysine (ForK; Wang et al, 2015), ε-N-propionyl-lysine (PrK; Gattner et al, 2013;Wilkins et al, 2015), ε-Nbutyryl-lysine (BuK; Gattner et al, 2013;Wilkins et al, 2015), ε-N-crotonyl-lysine (CrK; Gattner et al, 2013;Kim et al, 2012;Wilkins et al, 2015), ε-N-2-hydroxyisobutyryl-lysine (HibK; Xiao et al, 2015), ε-Nbenzoyl-lysine (BzK; Cao et al, 2021;Ji et al, 2021;Tian et al, 2021), ε-N-L-lactyl-lysine (LacK; Ren et al, 2022;Sun, Chen, Xu, et al, 2022), ε-N-β-hydroxybutyryl-lysine (BhbK; Ren et al, 2022), ε-N-lipoyl-lysine (LipoK; Ren et al, 2022), ε-N-heptanoyl-lysine (HepoK; Fu et al, 2019), and ε-N-(L-threonyl)-lysine (ThrK; Zang et al, 2022), have been developed and site-specifically incorporated into proteins in bacterial cells, enabling the production of recombinant acylation-bearing proteins such as core histone proteins H2B, H3, and H4. As a recent example for functional studies, Wan et al prepared recombinant fructose-bisphosphate aldolase A (ALDOA) with site-specific lactylation, a newly identified type of lysine acylation in histone and non-histone proteins (Sun, Chen, & Peng, 2022;Zhang et al, 2019), and showed that K147 lactylation inhibits the activity of this glycolytic enzyme (Wan et al, 2022).…”
Section: Lysine Acylationmentioning
confidence: 99%
“…Taking advantage of the substrate promiscuousness of the Pyl pairs, various acylation-bearing UAAs (Figure 2b), that is, ε-N-acyl-lysines, such as ε-N-formyllysine (ForK; Wang et al, 2015), ε-N-propionyl-lysine (PrK; Gattner et al, 2013;Wilkins et al, 2015), ε-Nbutyryl-lysine (BuK; Gattner et al, 2013;Wilkins et al, 2015), ε-N-crotonyl-lysine (CrK; Gattner et al, 2013;Kim et al, 2012;Wilkins et al, 2015), ε-N-2-hydroxyisobutyryl-lysine (HibK; Xiao et al, 2015), ε-Nbenzoyl-lysine (BzK; Cao et al, 2021;Ji et al, 2021;Tian et al, 2021), ε-N-L-lactyl-lysine (LacK; Ren et al, 2022;Sun, Chen, Xu, et al, 2022), ε-N-β-hydroxybutyryl-lysine (BhbK; Ren et al, 2022), ε-N-lipoyl-lysine (LipoK; Ren et al, 2022), ε-N-heptanoyl-lysine (HepoK; Fu et al, 2019), and ε-N-(L-threonyl)-lysine (ThrK; Zang et al, 2022), have been developed and site-specifically incorporated into proteins in bacterial cells, enabling the production of recombinant acylation-bearing proteins such as core histone proteins H2B, H3, and H4. As a recent example for functional studies, Wan et al prepared recombinant fructose-bisphosphate aldolase A (ALDOA) with site-specific lactylation, a newly identified type of lysine acylation in histone and non-histone proteins (Sun, Chen, & Peng, 2022;Zhang et al, 2019), and showed that K147 lactylation inhibits the activity of this glycolytic enzyme (Wan et al, 2022).…”
Section: Lysine Acylationmentioning
confidence: 99%
“…25,26 One such reaction is lysine (Lys) acylation, where Lys acetylation is critical for histones and in other contexts, [27][28][29][30] and many longer-chain Lys acylation PTMs [31][32][33] such as malonylation, 34,35 succinylation, 34,36 and glutarylation 37,38 have been discovered yet are poorly understood. 39 As an alternative to approaches that include introduction of Lys analogues, [40][41][42][43] nonsense codon suppression, [44][45][46][47][48][49] bottom-up ligation-based assembly strategies, [50][51][52] or enzymatic methods that typically require creation of a non-native protein by insertion of a specific target sequence, [53][54][55][56][57][58] DNAzymes are promising for top-down introduction of Lys acylation PTMs onto intact native proteins, [59][60][61][62][63][64][65] but only if DNAzymes can be identified with the fundamental catalytic ability of Lys acylation.…”
Section: Introductionmentioning
confidence: 99%